The Nottingham-Ice cream project: dietary intake, food waste and ice cream solutions - Marsh, Kirandeep (2023)
Older adults with fragility hip and spine fractures are often extremely frail and vulnerable to malnutrition. Malnutrition is a debilitating condition in these patients. Prescription of oral nutritional supplements (ONS) is recommended to improve dietary intake.